The Relationship Between The University And Industrial Institutions And Its Impact On Scientific Research In Syria (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The objective of this study was to assess the assessment of the teachers of The aim of this study was to assess the relationship between the university and the economic and social development institutions and their impact on scientific research in Syria. It is worth mentioning the strategy adopted by the university on the one hand and the developmental institutions on the other, and the evaluation of the relationship between them for the service of scientific research and therefore development in Syria. We used the descriptive analytical method, and relied on the questionnaire to find out the opinions of the respondents, by drawing a random sample of 356 teaching staff members in the Syrian universities and 374 public and private industrial institutions. And then unload the responses by statistical program SPSS.23, And data analysis by statistical methods, and draw conclusions, the most important of which are: - Syrian university procedures do not serve the scientific research process. - The procedures of industrial establishments do not serve the scientific research process. - The relationship between the university and industrial institutions does not serve the scientific research process. هدفت هذه الدراسة إلى تقييم العلاقة بين الجامعة و المؤسسات الصناعية الاقتصادية و الاجتماعية وانعكاسها على البحث العلمي في سورية . و ذلك من خلال الاطلاع على الاجراءات التي تنتهجها  الجامعة من جهة  والمؤسسات الصناعية من جهة أخرى ، و تقييم العلاقة بينهما لخدمة البحث العلمي و بالتالي التنمية في سورية. استخدمنا في هذا البحث المنهج الوصفي التحليلي، و اعتمدنا على الاستبانة لمعرفة آراء المبحوثين ، من خلال سحب عينة عشوائية تضمنت 356 عضو هيئة تدريسية في الجامعات السورية ، و 374 مؤسسة صناعية عامة وخاصة  . ثم تفريغ الاستجابات بواسطة البرنامج الاحصائي SPSS.23 ، و تحليل البيانات بواسطة الأساليب الاحصائية ، و استخلاص النتائج التي كان من أهمها ما يلي : - اجراءات الجامعة السورية لا تخدم عملية البحث العلمي. - اجراءات المؤسسات الصناعية لا تخدم عملية البحث العلمي . - العلاقة بين الجامعة و المؤسسات الصناعية لا تخدم عملية البحث العلمي .